Vibrational (Infrared, Raman) and Thermogravimetric Study of Copper Ore from the Deposit at Tchirozerine, Agadez (Niger) - SANDA BAWA, Ali (European Journal of Applied Sciences, 2022)
Agadez is the mining region of the republic of Niger in which all kinds of ore are found. Copper would have been exploited and refined in Niger in the 15th century in the province of Azelik, region of Agadez. In this context, it is important to use mew techniques to characterize the mineralogical variability of copper ore. The collected sample was analyzed by X-ray diffraction, Thermogravimetric analysis and spectroscopies (infrared and Raman). The results of the X-ray diffraction of the ore show that the sample corresponds to an association between brochantite and biotite, dominated by brochantite. The thermogravimetric analysis indicates that the sample was stable up to 200°C and above this temperature, the solid decomposed in a series of three decomposition stages. Raman and infrared spectroscopies show the fundamental vibration of sulfate ion which functioning as a unidentate because the effective symmetry is lowered to C3v.